A Security Scheme for Protecting Agent Societies - Muñoz, Antonio (Review of Computer Engineering Research, 2018)
Mobile agent paradigm, in particular multi-agent systems represent a promising technology for emerging Ambient Intelligent scenarios and Cyber Physical Systems sharing a huge number of heterogeneous devices interacting. Unfortunately, the lack of appropriate security mechanisms, both their enforcement and usability, is hindering the application of this paradigm in real world applications. This paper presents a software based solution for the protection of multi-agent systems based on mobility property of agents. This approach focuses on the cooperative agent-based model and the core of this concept is the protected computing approach. Finally, one aspect of this approach is its user friendly style for agent based system developers who are not security experts.